Secondary physical education, participation by sex in moderate to vigorous physical activity (Educación física en secundaria, participación por sexo en actividad física moderada a vigorosa) - Hall-López, Javier Arturo (Retos, 2020)
Abstract. Objective: To compare by sex the participation in moderate to vigorous physical activity in secondary school physical education classes. Method: The research design was comparative descriptive, with convenience sampling, 188 adolescents with an average age of 12.5 ± 0.7 enrolled in public secondary schools in the city of Mexicali, Baja California participated. Mexico. The system for observing fitness and instruction time (SOFIT) was used to determine the moderate to vigorous physical activity of 47 physical education classes. Results: The equality of the variance was calculated by the Student t test for independent samples less than α≤ 0.05; finding significant differences of participation in vigorous moderate physical activity lower in women than in men during physical education class (P-Value = .002) with a difference percentage of 32.5 (Δ%) between men and women. Conclusion: In a constructive way, it is recommended to take pedagogical actions with cooperative and simultaneous participation of students in moderate to vigorous physical activity for at least 50% of class time, and guide educational content to involve students in the movement both genders, as established by UNESCO to provide quality physical education. Resumen. Objetivo: Comparar por sexo la participación en actividad física moderada a vigorosa en clases de educación física de secundaria. Método: El diseño de la investigación fue descriptivo comparativo, con muestreo por conveniencia, participaron 188 adolescentes de una edad promedio de 12.5±0.7 matriculados en secundarias públicas de la ciudad de Mexicali, Baja California. México. Se utilizó como instrumento de evaluación el Sistema para observar el tiempo de instrucción de actividad física (SOFIT), para determinar la actividad física moderada a vigorosa de 47 clases de educación física. Resultados: La igualdad de la varianza se calculó mediante la prueba t-Student para muestras independientes resultando por sexo menor a α≤ 0.05; encontrando diferencias significativas de participación en actividad física moderada vigorosa menores en mujeres que en hombre durante la clase de educación física (P-Valor=.002) con un porcentaje de diferencia de 32.5 (Δ%) entre hombres y mujeres. Conclusión: De manera constructiva, se recomienda tomar acciones pedagógicas con participación cooperativa y simultanea de los estudiantes en actividad física moderada a vigorosa por lo menos el 50% del tiempo de la clase, y guiar contenidos educativos para involucrar en el movimiento a los estudiantes de ambos géneros, como lo establece la UNESCO para brindar una educación física de calidad.